Manajemen Aset Dan Strategi Pemanfaatan Hak Kekayaan Intelektual (Hak Cipta Sebagai Aset Tak Berwujud) - Adhitya, Arya (Technology and Economics Law Journal, 2023)
Assets are one of the results of activities carried out by government agencies. One of these assets can be intellectual property rights (IPR), as intangible assets. IPR is one of the results of thinking or creativity of the State Civil Apparatus (ASN) in official relations with Government Agencies. These IPRs are managed as assets belonging to government agencies. Management of IPR Assets is still not managed well, correctly and ideally. The implementation of IPR asset management needs to be carried out and maximized in order to provide benefits. One of the benefits generated is the economic benefits of the owners and holders of IPR, as well as to parties who have an interest in and utilize the IPR. The form of utilization, the strategy determined, and the role of government agencies are important things to study in depth so that a good, correct and ideal IPR asset management formula is obtained in government agencies. This research was carried out by taking an approach based on statutory regulations, legal and non-legal theories, books and related literature, in order to gain understanding and provide the expected and proper results from a form of IPR asset management.